2012
DOI: 10.1186/1479-5876-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose treatment suppresses inflammation, oxidative stress, and vasospasm induced by experimental subarachnoid hemorrhage

Abstract: BackgroundSubarachnoid hemorrhage (SAH) frequently results in several complications, including cerebral vasospasm, associated with high mortality. Although cerebral vasospasm is a major cause of brain damages after SAH, other factors such as inflammatory responses and oxidative stress also contribute to high mortality after SAH. Trehalose is a non-reducing disaccharide in which two glucose units are linked by α,α-1,1-glycosidic bond, and has been shown to induce tolerance to a variety of stressors in numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 42 publications
7
84
0
Order By: Relevance
“…It has also been suggested to have antiinflammatory, anti-oxidative stress, and anti-apoptotic effects [34][35][36]. These roles, coupled with anti-aggregation properties and lack of toxicity, enhance the potential translational value of trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested to have antiinflammatory, anti-oxidative stress, and anti-apoptotic effects [34][35][36]. These roles, coupled with anti-aggregation properties and lack of toxicity, enhance the potential translational value of trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…Brain subarachnoid bleeding in humans and experimental animals, resulting from events such as ruptured aneurysms or brain injury, triggers inter-related pathomechanisms partially attributable to the release of toxic byproducts of hemoglobin degradation, [10][11][12] leading to irreversible brain damage and even death. Delayed ischemic neurological deficit is recognized as the most prominent complication of brain subarachnoid bleeding, 10,12 and has been associated to several mechanisms including vasospasms, 10 failure of blood flow autoregulation, 7 disruption of the blood-brain barrier, 12 edema, 12 microthrombosis, 13 inflammation 11 and oxidative stress, 10 among others.…”
Section: Possible Implications Of Ssb On Sci Outcomementioning
confidence: 99%
“…Delayed ischemic neurological deficit is recognized as the most prominent complication of brain subarachnoid bleeding, 10,12 and has been associated to several mechanisms including vasospasms, 10 failure of blood flow autoregulation, 7 disruption of the blood-brain barrier, 12 edema, 12 microthrombosis, 13 inflammation 11 and oxidative stress, 10 among others. Conditions such as these can in turn lead to alterations in neuronal signal processing and transmission, 12 infarctions 6 and gliosis.…”
Section: Possible Implications Of Ssb On Sci Outcomementioning
confidence: 99%
“…As another pivotal signaling pathway, NF-κB pathway has been deemed to play a dominating role in inflammation post-SAH, which could be activated due to excess ROS generation. Accumulating evidence demonstrated that many agents (recombinant osteopontin, urinary trypsin inhibitor, trehalose, progesterone, et al) alleviated inflammatory response after SAH, partially via inhibiting NF-κB inflammatory pathway [24][25][26][27]. NLRP3 inflammasome is another key component of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%